2011
DOI: 10.28945/1383
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Digital Literacy through Web-based Collaborative Inquiry Learning – A Case Study

Abstract: Digital literacy (DL), a term that emerged with the explosion of digital information and multimedia technology, refers to basic competence in using digital technology. The present study first analyzed the evolvement from media literacy to digital literacy and developed a four-branch theoretical framework of DL by investigating related definitions of it. For the purpose of fostering DL, a set of web-based collaborative inquiry learning (WCIL) activities was designed and were implemented on weblog to further the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…The problems related to the lack of leadership in the group (Fu & Pow, ; Pauli et al., ; van Aalst et al., ) did not arise as a real issue in our data. Each group had a leader who was responsible for reporting work done at some points in the project.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The problems related to the lack of leadership in the group (Fu & Pow, ; Pauli et al., ; van Aalst et al., ) did not arise as a real issue in our data. Each group had a leader who was responsible for reporting work done at some points in the project.…”
Section: Discussionmentioning
confidence: 52%
“…The teacher did not allocate specified roles for group members but it turned out that in the actively collaborating groups one of the members had taken on leadership status. In a similar study Hong Kong, Fu and Pow () found that all groups showing active collaboration had a recognized leader. The reverse did not hold: Some recognized leaders failed to activate other members to collaborate and had to make most of the work alone.…”
Section: Related Researchmentioning
confidence: 91%
See 1 more Smart Citation
“…The increasing importance of digital media and technology in daily life has resulted in steady evolution of people's understanding of the concept of DL. Consequently, research about DL and DL education has received much attention in recent years (Erstad, 2007;Fu & Pow, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, for students to acquire a set of knowledge, skills, and attitudes to cope with the demands of today's knowledge society, "a learning process is needed that is focused on the activities that the students carry out and on the skills they acquire while performing them, rather than on the content itself" (Guitert & Romeu, 2009, p. 3). This study starts with problems and difficulties identified in a published case study of WCIL learning (Fu & Pow, 2011), explores the possible measures to deal with these problems and difficulties for full exertion of the effect of WCIL in developing students' DL, and sums these measures into a preliminary implementation strategy model.…”
Section: Introductionmentioning
confidence: 99%